Effect of β-Mannanase Supplementation on Growth Performance, Ileal Digestibility, Carcass Traits, Intestinal Morphology, and Meat Quality in Broilers Fed Low-ME Diets - Muhammad Umar Yaqoob; Muhammad Yousaf; Muhammad Issa Khan; Minqi Wang (Animals, 2022)
Experiment was designed to analyze the effect of low caloric diets, supplemented with β-mannanase on growth performance, carcass characteristics, nutrient digestibility, and other parameters in broilers. In this study, 400 broiler chicks were randomly divided into four treatments (Cont: without β-mannanase; LM-30, MM-60, and HM-90: supplemented with 200, 400, and 600 mg/kg β-mannanase, respectively). Dietary metabolizable energy (ME) in Cont was standard (starter diet 3100 kcal/kg; finisher diet 3200 kcal/kg) and reduced by 30, 60, and 90 kcal/kg, correspondingly in β-mannanase-supplemented treatments. The results exhibited that growth performance was not affected by reducing dietary energy levels with supplementation of β-mannanase. Ileal digestibility of DM and CF was improved (p < 0.01) by supplementation of β-mannanase at low dietary ME levels. Concerning carcass traits, the relative weight of breast meat, drumstick, and abdominal fat increased (p < 0.05) with β-mannanase supplementation in low-ME diets. Treatment HM-90 showed significantly (p < 0.05) better results regarding villus height and VH:CD. It could be concluded from the present results that supplementation of β-mannanase could improve the nutrient digestibility so that it is possible to reduce the dietary energy level without compromising production performance, carcass trails, and meat quality in broilers.